Komunikasi Menjadi Salah Satu Cara Efektif Dalam Pendidikan di TK An Nizam - Barus, Melianna Br; Pulungan, Nailah; Afifah, Nida; Nasution, Arifah; Anggraini, Elya Siska (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Effective communication is a fundamental element in the learning process. The interactions that exist between educators and students, as weel as between students, become the basis for transferring knowledge, instilling values, and developing character. However, in practice, effective communication in education still often encounters obstacles. This can be caused by various factors, such as educators’ lack of understanding of effective communication strategies, lack of preparation and practice, as weel as cultural and language barriers. This research aims to analyze the importance of effective communication in education. identifying key elements in effective communication in education. Developing strategies to build effective communication in education. This research uses qualitative methods. The results of the research show that effective communication in education has a very important role in increasing learning motivation, understanding of the material, and active participation of students.